BANTUAN PNPM MANDIRI DALAM BIDANG SIMPAN PINJAM BAGI PEREMPUAN DI NAGARI SUNGAI LIKU KECAMATAN RANAH PESISIR KABUPATEN PESISIR SELATAN - Nengsih, Afrina; Dasrizal, Dasrizal; Zuriyani, Elvi (Pendidikan Geografi, 2013)
This study aims to determine the PNPM Mandiri assistance in the areas of savings and loans for women in Nagari Sungai Liku Ranah Pesisir Distric Pesisir Selatan. Type of research is descriptive. Population is female participants in the field of PNPM Mandiri savings and loans for women in 2012 contained in Nagari Sungai Liku Ranah Pesisir Distric Pesisir Selatan, amounting to 164 people. Sample respondents taken proportional random sampling technique with 40% of the number of members of savings and loans in Nagari Sungai Liku Ranah Pesisir Distric Pesisir Selatan. The research found that: 1) Distribution of group savings and loan recipients PNPM Mandiri is uneven in every village in Nagari Sungai Liku, where there is a little village with a number of recipients, 2) Criteria for households who want to join the activities of savings and loans of PNPM Mandiri ie households who are poor and households who want to join the activities PNPM Mandiri Credit ie household trustworthy and able to repay the borrowed funds, 3) distribution system grants in the field of PNPM Mandiri PNPM Mandiri Credit in Nagari Sungai Liku include distributing by way of distributed directly into the field with the number varies between Rp 1,000,000 - Rp 5.000.000/anggota, while the use of savings and loan mostly used for trade and capital 4) Way way aid refund PNPM Mandiri Savings and Loans is quite easy and simple. Each household member or participating activities PNPM Mandiri Credit directly or simply submit the group leader and group leader immediately handed over to the treasurer of the group, with the agreed time limit. Once the funds collected, each group directly handed to the UPK district, represented by chairman and treasurer.